2009
DOI: 10.1007/s12204-009-0443-2
|View full text |Cite
|
Sign up to set email alerts
|

A study on dynamic response of cable-seabed interaction

Abstract: A numerical method is developed to investigate the dynamic response of cable-seabed interaction in this paper. The motion of cable is described by the Lumped Parameter Method, while the seabed, unlike the prevailing simplified model of elastic foundation, is modeled as an irregular continuous rigid surface with rebound and friction existing, and the forces exerted by the seabed consist of normal counterforce and isotropic tangential Coulomb friction resistance. To describe the detailed dynamic response, two co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Wang et al [10] used the lumped mass approach to model a mooring line in conjunction with a seabed model based on rigid body collision analysis. It was noted by the authors that, upon line impact with the seabed, there were fluctuations in the fairlead tension which they attributed to the spatially discrete nature of the line structural model.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [10] used the lumped mass approach to model a mooring line in conjunction with a seabed model based on rigid body collision analysis. It was noted by the authors that, upon line impact with the seabed, there were fluctuations in the fairlead tension which they attributed to the spatially discrete nature of the line structural model.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies have suggested that the spring mattress model is prone to discretisation errors associated with line contact with the seabed, particularly spurious tension fluctuations as noted by Refs. [112,113]. The dependence of these models on force coefficients which are difficult to define and calibrate for various seabed and case-specific environmental excitation conditions is an area where further work is required.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [113] used the lumped mass approach to model a mooring line in conjunction with a seabed model based on rigid body collision analysis. It was noted by the authors that, upon line impact with the seabed, there were fluctuations in the fairlead tension which they attributed to the spatially discrete nature of the line structural model.…”
Section: Seabed Interaction Modelsmentioning
confidence: 99%